Role of Soluble CD23 in Patients with Hyperthyroidism: Case–Control Study - Salim Hussein Hassan; Aqeel S. Abd Al-Salam; Nawras A. Esmaeel (Medical Journal of Babylon)
Background: Hyperthyroidism, or Graves’ disease (GD), is the consequence of an overproduction of thyroid hormones. Objective: This study aimed to determine the concentration of soluble CD23 in GD patients and the correlation of its level with biomarkers (T.3, T.4, thyroid stimulating hormone [TSH], FT.3, FT.4, and vitamin D, among those. Materials and Methods: There were eighty patients (50 patients with hyperthyroidism and 30 controls), during the time frame beginning in February 2021 and ending in April 2022 at Karbala city. In this research, participants were required to have a positive result on both an ultrasound of the thyroid and a test for thyrotropin receptor autoantibody (TRAB). FT.3, FT.4, and TRAB. Levels were determined by the VIDAS technique. Serum sCD23 and vitamin D3 levels were determined by ELISA using commercial test kits. Results: The mean age of the patients included in this study was 39 ± 12 years, while that of the control group was 30 ± 10 years. GD was noticed among female more than male patients. Regarding the age groups of GD, more patients were in the 25–44 years age group than in the other age groups. The immunological marker sCD23 is higher in the patients’ group when compared with the control group (486.16 ± 185.39, 166.64 ± 61.15, respectively) and no correlation between levels of it and T3, T4, TSH, and vitamin D. Conclusion: There was a statistically significant difference between the patient and control groups in the levels of sCD23 and thyroid panel test.